Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/nu14030584
|View full text |Cite
|
Sign up to set email alerts
|

Lactose Malabsorption and Presumed Related Disorders: A Review of Current Evidence

Abstract: Background. Lactose malabsorption (LM) is a frequent clinical problem associated with several digestive and extra-digestive diseases. The aim of this manuscript was to clarify the real clinical impact of LM on these disorders. Methods. A literature search for digestive and extra-digestive disorders related to LM was carried out using PubMed, Medline and Cochrane. Results. A transient lactase deficiency is present in celiac disease (CD) on a normal diet. The persistence of symptoms in CD on a gluten-free diet m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 47 publications
(85 reference statements)
0
8
0
1
Order By: Relevance
“…Chemically, it is a disaccharide of glucose and galactose linked by a β-1-4 glycosidic bond between the carbon 4 of glucose and carbon 1 of galactose ( 16 , 17 ). Under normal circumstances, following consumption, it is hydrolyzed by the enzyme lactase (β-galactosidase) in the proximal small intestine into the monosaccharides glucose and galactose which are then absorbed ( 16 18 ). However, it has been found that not all lactose is metabolized and absorbed in the small intestine, and some dietary lactose may enter the colon ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…Chemically, it is a disaccharide of glucose and galactose linked by a β-1-4 glycosidic bond between the carbon 4 of glucose and carbon 1 of galactose ( 16 , 17 ). Under normal circumstances, following consumption, it is hydrolyzed by the enzyme lactase (β-galactosidase) in the proximal small intestine into the monosaccharides glucose and galactose which are then absorbed ( 16 18 ). However, it has been found that not all lactose is metabolized and absorbed in the small intestine, and some dietary lactose may enter the colon ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…Prior to its absorption, lactose needs to be hydrolyzed in the gastrointestinal tract of humans into two components with the action of an enzyme known as lactase. The enzyme lactase-phlorizin hydrolase (lactase) is mainly expressed in the brush border of the intestinal villi where it resides on the membrane of enterocytes (Misselwitz et al 2019;Usai-Satta et al 2022). Two identical polypeptide chains of size 160 kDa are combined with the intra cytoplasmic part to make up this enzyme and it shows the optimum activity at a pH between 6 and 8 in the small intestine.…”
Section: Lactose Malabsorptionmentioning
confidence: 99%
“…Die Therapie der Wahl ist eine gute individualisierte Ernährungsberatung und eine laktose-, fruktose- oder sorbitarme Kost 1 . Ein völliger Verzicht auf diese Kohlenhydrate ist weder sinnvoll noch praktikabel, laktoseintolerante Patienten vertragen i.d.R.…”
Section: Was Kann Sich Hinter Dem Reizdarmsyndrom Verstecken?unclassified